The influence of day 3 embryo cell number on the clinical pregnancy and live birth rates of day 5 single blastocyst transfer from frozen embryo transfer cycles - Jie Wang; Zhenyu Diao; Junshun Fang; Lihua Zhu; Zhipeng Xu; Fei Lin; Ningyuan Zhang; Linjun Chen (BMC, 2022)
Abstract Background To evaluate the influence of day 3 embryo cell number on the clinical pregnancy and live birth rates of day 5 single blastocyst transfer in frozen embryo transfer (FET) cycles. Methods Our retrospective study included 3761 day 5 single blastocyst FET cycles between January 2015 and December 2019. These FET cycles were divided into three groups according to the day 3 embryo cell number: 939 cycles in the < 8-cell group, 1224 cycles in the 8-cell group and 1598 cycles in the > 8-cell group. The clinical pregnancy and live birth rates were compared among the three groups. Results The clinical pregnancy rate of day 5 single blastocyst transfer in FET cycles increased significantly as the day 3 embryo cell number increased (52.2%, 61.4% and 66.8%, P < 0.001). Similarly, the live birth rate increased significantly as the day 3 embryo cell number increased (42.7%, 49.8% and 54.9%, P < 0.001). The results of the subgroup analysis showed that the clinical pregnancy and live birth rates were not significantly different among the three groups when good-quality blastocysts were transferred. The clinical pregnancy and live birth rates increased significantly as the day 3 embryo cell number increased when fair- and poor-quality blastocysts were transferred. Conclusion The day 3 embryo cell number needs to be considered when day 5 single blastocyst transfer is performed in FET cycles, especially when fair- and poor-quality blastocysts are used for transfer. The transfer of a day 5 single blastocyst derived from an embryo with faster development on day 3 may shorten the time to achieving a live birth.